High prevalence of extended-spectrum beta-lactamase-producing Klebsiella pneumoniae and Escherichia coli in clinical infections in a tertiary care hospital in southwestern Nigeria - Oluwatoyin Akinde; Babatunde Odetoyin (Microbiologia Medica, 2025)
Background: Extended-Spectrum Beta-Lactamase (ESBL)-producing Klebsiella pneumoniae and Escherichia coli infections significantly impact healthcare delivery and contribute to global antibiotic resistance. Thus, knowledge of their prevalence and risk factors is essential for quick and effective treatment, prevention, and management. In this study, we investigated the prevalence of ESBL production among clinical K. pneumoniae and E. coli isolates, determined their susceptibility profile, and identified risk factors associated with their infections in a tertiary care hospital.